Impelementasi Impelementasi Keberlanjutan Baitul Maal Wa At Tamwi: - Muhammad Garamatan; Hendri Tanjung; Ibdalsyah Ibdalsyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is about the sustainability of Baitul Maal wa At Tamwil by using two variables, namely financing growth and human resources. Sharia economic discourse in the field of sharia microfinance institutions is interesting and needs to be developed in encouraging national economic growth, as well as a forum to encourage small entrepreneurs to grow both from their business and the household economy. This study uses a qualitative approach, research that seeks to provide an objective description of the object under study, as well as interpret and give meaning to empirical data in the field. The object of this research is KSPPS Khidmatul Ummah Bogor, which is located in Cibungbulang District, Bogor Regency. The results of this study are institutionally KSPSS Khidmatul Ummah Bogor is a sharia microfinance institution incorporated as a Sharia Savings and Loans Financing Cooperative on a Primary Scale District, which is engaged in empowering the poor and unbankable by carrying out social functions in Biatul Maal and business functions (tijari) through Baitul at Tamwil KSPSS Khidmatul Ummah. It is intended to be able to solve the economic problems of the lower middle class community in West Bogor, Bogor Regency. Mudharabah contract financing growth is able to encourage KSPPS Khidmatul Ummah to continue to exist in providing microfinance services to members to the maximum, as well as providing loan services to members with qard hasan contracts as an effort to encourage the growth of member independence. As well as in realizing institutional sustainability, KSPPS Khidmatul Ummah formed Human Resources with the characters of Shiddiiq, Amanah, Tabligh and Fathanah, with routine education methods that are ubudiyah routines and providing religious and muamalah materials to employees. Keywords: Baitul Maal wa At Tamwil, Sustainability, Operations